Automated digital counselling with social network support as a novel intervention for patients with heart failure: protocol for randomised controlled trial. Issue 9 (5th September 2022) - Peiris, Rachel Grace; Ross, Heather; Chan, Christopher T; Poon, Stephanie; Auguste, Bourne Lewis; Rac, Valeria E; Farkouh, Michael; McDonald, Michael; Kaczorowski, Janusz; Code, Jillianne; Duero Posada, Juan; Ong, Stephanie; et al.
Abstract : Introduction: Heart failure (HF) symptoms improve through self-care, for which adherence remains low among patients despite the provision of education for these behaviours by clinical teams. Open Access Digital Community Promoting Self-Care, Peer Support and Health Literacy (ODYSSEE–vCHAT) combines automated digital counselling with social network support to improve mortality and morbidity, engagement with self–care materials, and health-related quality of life. Methods and analysis: Use of ODYSSEE-vCHAT via Internet-connected personal computer by 162 HF patients will be compared with a control condition over 22 months. The primary outcome is a composite index score of all-cause mortality, all-cause emergency department visits, and HF-related hospitalisation at trial completion. Secondary outcomes include individual components of the composite index, engagement with self-care materials, and patient-reported measures of physical and psychosocial well-being, disease management, health literacy, and substance use. Patients are recruited from tertiary care hospitals in Toronto, Canada and randomised on a 1:1 ratio to both arms of the trial. Online assessments occur at baseline (t=0), months 4, 8 and 12, and trial completion. Ordinal logistic regression analyses and generalised linear models will evaluate primary and secondary outcomes. Ethics and dissemination: The trial has been approved by the research ethics boards at the University Health Network (20-5960), Sunnybrook Hospital (5117), and Mount Sinai Hospital (21-022-E). Informed consent of eligible patients occurs in person or online. Findings will be shared with key stakeholders and the public. Results will allow for the preparation of a Canada-wide phase III trial to evaluate the efficacy of ODYSSEE-vCHAT in improving clinical outcomes and raising the standard of outpatient care. Trial registration number: NCT04966104